IMPLEMENTASI METODE FIFO DALAM PERHITUNGAN NILAI PERSEDIAAN PADA PT.X DISTRIBUTOR MAKANAN DI JAWATIMUR - Annisa Rahmawati; Achmad Daengs GS (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Inventory is a set of assets held for resale. The assessment of the value of inventories has an important role in two financial reports at the same time, namely in the presentation of the balance sheet and the exposure in the income statement. In general, the inventory valuation method is divided into three, namely First In First Out, Last in First Out and Average. PSAK No. 14 states that except for companies that have inventories that are specially produced and cannot be replaced with other inventories, these inventories are usually valued using the First In First Out method. PT X is a snack food distributor company in East Java which conducts an inventory assessment using the Last In First Out method, which is not in accordance with the exposure of PSAK No. 14. This research was conducted using a descriptive qualitative method. This study aims to present the results of the implementation of the First In First Out inventory valuation method at PT X. The results of this study explain that the implementation of the First In First Out valuation method can provide a more reasonable exposure to inventory valuation because companies with inventory classified as easily damaged such as PT X, the First In First Out method can provide inventory valuation exposure that is adjusted to the movement of goods in and out.